2008
DOI: 10.1111/j.1365-2222.2008.02949.x
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous sensitization with Dermatophagoides farinae induces generalized allergic dermatitis and elevated mite‐specific immunoglobulin E levels in a canine model of atopic dermatitis

Abstract: This study demonstrated that epicutaneous application of HDM slurry to MAB dogs results in elevations of HDM-specific IgE, localized and generalized pruritic dermatitis resembling spontaneous canine AD, and histologic changes typical of IgE-driven inflammation. We feel that these results suggest that epicutaneous exposure to allergen may play an important role during both the sensitization and the perpetuation of AD, and provide support for the use of a canine model in the investigation of the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 38 publications
5
61
1
Order By: Relevance
“…In AD, inflammation is characterised by an influx of CD4 + and CD8 + T cells in the lesional skin (Olivry et al, 1997;Sinke et al, 1997) and a mixed cytokine profile with predominant expression of IL-6, TARC, IL-4 and IL-13 genes in the early stage followed by IFN-c, IL-12 and IL-18 later on (Olivry et al, 1999;Nuttall et al, 2002;Marsella et al, 2006). Whereas most dogs with AD have circulating allergen-specific IgE (DeBoer and Hillier, 2001), there is controversial evidence for a similar reaction phenomenon in dogs with spontaneous manifestations of CAFRs (Jackson et al, 2003;Pucheu-Haston et al, 2008;Puigdemont et al, 2006). Increasing our insight in the immunopathogenesis of CAFRs may facilitate the development of novel modalities to treat them.…”
Section: Introductionmentioning
confidence: 99%
“…In AD, inflammation is characterised by an influx of CD4 + and CD8 + T cells in the lesional skin (Olivry et al, 1997;Sinke et al, 1997) and a mixed cytokine profile with predominant expression of IL-6, TARC, IL-4 and IL-13 genes in the early stage followed by IFN-c, IL-12 and IL-18 later on (Olivry et al, 1999;Nuttall et al, 2002;Marsella et al, 2006). Whereas most dogs with AD have circulating allergen-specific IgE (DeBoer and Hillier, 2001), there is controversial evidence for a similar reaction phenomenon in dogs with spontaneous manifestations of CAFRs (Jackson et al, 2003;Pucheu-Haston et al, 2008;Puigdemont et al, 2006). Increasing our insight in the immunopathogenesis of CAFRs may facilitate the development of novel modalities to treat them.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, immunofluorescent staining for Der f 1 has demonstrated that mite allergens could infiltrate subepidermal sites after epicutaneous application of Der f slurry in a model of canine AD [19], which suggests that the defective epidermal barrier in atopic skin may enhance penetration of HDM. Furthermore, epicutaneous sensitization with HDM allergens has been shown to induce elevation of mite-specific IgE and pruritic dermatitis, resembling spontaneous AD in dogs [19]. Additionally, atopy patch testing with HDM enhanced mRNA transcription of cytokines (IL-6, IL-12p35, IL-13, IL-18 and IFN-) and a chemokine, TARC/CCL17, in lesional skin from high-IgE Beagles [12].…”
mentioning
confidence: 99%
“…In this model, pruritus and dermatitis can be elicited after epicutaneous application of house dust mites [75]. Lesions are consistent with naturally occurring AD lesions [76,77] making it a suitable model to test new therapies.…”
Section: Dog Models Of Atopic Dermatitismentioning
confidence: 99%